(untitled) (Revista Contexto & Saúde, 2026)
To evaluate potential drug interactions in medical prescriptions issued at Psychosocial Care Centers. A retrospective, descriptive, documentary, and exploratory cross-sectional study with a quantitative approach, involving one hundred and seventy users from two psychosocial care services, all of whom were continuously using multiple medications. Prescriptions were analyzed to identify potential drug interactions. In all prescriptions evaluated, at least one potentially serious or contraindicated interaction was observed. The most commonly prescribed medications in these services included carbamazepine, sertraline, promethazine, diazepam, clonazepam, haloperidol, levomepromazine, and valproic acid. The frequent use of antipsychotics, anticonvulsants, and antidepressants was associated with an increased risk of clinically significant drug interactions. It is concluded that the use of multiple medications in the treatment of mental disorders is an established clinical practice; however, it is associated with elevated risks. The complex profile of patients receiving care requires an individualized therapeutic approach, taking into account comorbidities, socioeconomic vulnerability, treatment resistance, symptom diversity, potential adverse effects, and drug interactions with other medications and other substances.